1991
DOI: 10.1152/ajpheart.1991.261.5.h1659
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine clearance is increased during acute hypoxemia in humans

Abstract: Acute hypoxemia leads to activation of the sympathetic nervous system (SNS), yet adrenergic vasoconstriction does not occur and venous plasma norepinephrine (NE) fails to rise as expected. To examine whether this dissociation between SNS tone and plasma NE is due to altered metabolism of NE, we measured arterial NE kinetics ([3H]NE infusion technique) and sympathetic nervous outflow to muscle (peroneal microneurography) during 25-30 min of hypoxemia (spontaneous breathing, mean O2 saturation 74%) in six health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
108
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 0 publications
12
108
0
Order By: Relevance
“…Following 20-30 min acute exposure to a level of hypoxia of similar magnitude to that used in the present study, NA spillover was increased by 46 % while NA clearance was reduced by 20 % (Leuenberger et al 1991). The present study indicates that altitude acclimatisation results in a restoration of sea level NA clearance while spillover is remarkably elevated, reaching values similar to those reported, for example, in patients with compensated chronic heart failure (Azevedo et al 2000).…”
Section: Figure 1 Blood Pressure and Vascular Conductancessupporting
confidence: 85%
See 2 more Smart Citations
“…Following 20-30 min acute exposure to a level of hypoxia of similar magnitude to that used in the present study, NA spillover was increased by 46 % while NA clearance was reduced by 20 % (Leuenberger et al 1991). The present study indicates that altitude acclimatisation results in a restoration of sea level NA clearance while spillover is remarkably elevated, reaching values similar to those reported, for example, in patients with compensated chronic heart failure (Azevedo et al 2000).…”
Section: Figure 1 Blood Pressure and Vascular Conductancessupporting
confidence: 85%
“…A less accentuated elevation in NA spillover has been reported in acute hypoxia (Leuenberger et al 1991). Following 20-30 min acute exposure to a level of hypoxia of similar magnitude to that used in the present study, NA spillover was increased by 46 % while NA clearance was reduced by 20 % (Leuenberger et al 1991).…”
Section: Figure 1 Blood Pressure and Vascular Conductancessupporting
confidence: 52%
See 1 more Smart Citation
“…It is well documented that during systemic hypoxia, peripheral blood flow is increased. 1,3 In the present study, FBF was determined in 3 subjects to confirm this finding. It was observed that skeletal muscle blood flow was increased 1.3 mL ⅐ min Ϫ1 ⅐ 100 mL Ϫ1 , whereas in a study by Leuenberger et al 3 using exactly the same protocol, FBF was increased 1.2 mL ⅐ min Ϫ1 ⅐ 100 mL…”
Section: Discussionmentioning
confidence: 53%
“…To compensate for the decreased O 2 delivery to tissues, a number of mechanisms are activated, resulting in an increase in ventilation, heart rate, cardiac output, and peripheral (muscle) blood flow. [1][2][3] Although a number of different compounds have been suggested to be responsible for the hypoxia-induced increase in blood flow, the most widely recognized and investigated has been adenosine. Much of the previous work has used various heart models, 4 -6 and most of the evidence for a role of adenosine came from studies showing that hypoxia-induced hyperemia was attenuated by adenosine deaminase, 7 adenosine receptor blockade, 4 or the inhibition of adenosine production.…”
mentioning
confidence: 99%